A cultural theory of expertise: styles of thought in attitudes, beliefs, and expectations regarding the COVID-19 pandemic - Pellegrini, Pablo Ariel (2024)
This article aims to analyze attitudes towards the pandemic by finding correlations between them that can be used to identify different styles of thought. The research involved two surveys (with 5990 participants) conducted in Argentina during the period of isolation regulations. These surveys assessed people’s attitudes toward the pandemic, their beliefs, fears, and expectations. We can group the people surveyed into three styles of thought, represented by those who believe in a natural origin of the virus, those who believe it leaked by accident from a laboratory, and those who believe it was intentionally released, all three distributed equally among the Argentine population. An important finding of this work is how attitudes are articulated within each style of thought: each group has its own defined position regarding the inquired issues, that is, its own ideological matrix, a different opinion on vaccines, science, and the pandemic. We referred to these three styles of thought in relation to the pandemic as open-to-expertise, nihilist, and self-expertise-only. Articulating perspectives from anthropology and the sociology of knowledge, our analysis proposes a cultural theory of expertise as a model to analyze the different attitudes found in the public sphere regarding the pandemic and other debates. According to the cultural theory of expertise we propose, how people perceive expertise shapes their thoughts and influences their opinions about phenomena in which reliance on others’ knowledge is crucial.